1998
DOI: 10.1128/aac.42.12.3315
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Activities of Several Diaminomethylpyridopyrimidines against Mycobacterium avium Complex

Abstract: Three recently synthesized dihydrofolate reductase (DHFR) inhibitors designated SoRI 8890, 8895, and 8897 were evaluated for their in vitro activities against 25 isolates of Mycobacterium avium complex. The MICs at which 50 and 90% of isolates were inhibited were 1 and 2, 4 and 8, and 4 and 8 μg/ml for SoRI 8890, 8895, and 8897, respectively. Although the addition of dapsone at 0.5 μg/ml did not significantly enhance the in vitro activities of these compounds, their activities alone were comparable to, if not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…However, there are some flaws for these drugs such as: (i) the therapeutic efficacy of RBT against MDR-TB is somewhat flawed because of the anti-RBT cross-resistance, which is acquired by the majority of RFP-resistant MTB isolates [33]. Similar data are also reported for RPT and RLZ [20,34]; (ii) all the FQs possess only modest antituberculous activity in treating TB, whereas quinolone-resistant MTB strains are rapidly increasing [30,32,[35][36][37][38]. In addition, although a number of new FQs have been synthesized and developed as chemotherapeutic drugs against common bacterial infections (e.g., sitafloxacin, gatifloxacin, moxifloxacin, grepafloxacin, WQ-3034, HSR-903, T-3811, etc.…”
Section: Introductionmentioning
confidence: 74%
“…However, there are some flaws for these drugs such as: (i) the therapeutic efficacy of RBT against MDR-TB is somewhat flawed because of the anti-RBT cross-resistance, which is acquired by the majority of RFP-resistant MTB isolates [33]. Similar data are also reported for RPT and RLZ [20,34]; (ii) all the FQs possess only modest antituberculous activity in treating TB, whereas quinolone-resistant MTB strains are rapidly increasing [30,32,[35][36][37][38]. In addition, although a number of new FQs have been synthesized and developed as chemotherapeutic drugs against common bacterial infections (e.g., sitafloxacin, gatifloxacin, moxifloxacin, grepafloxacin, WQ-3034, HSR-903, T-3811, etc.…”
Section: Introductionmentioning
confidence: 74%
“…gondii may be useful as drugs against M . avium complex has recently been suggested in two other reports. 14b, …”
Section: Biochemical and Biological Assaysmentioning
confidence: 84%
“…Similarly, Rosowsky et al synthesized 2,4-diaminopteridine analogues with a bridged diarylamine side chain and found that the compound having seven-membered ring in the dibenz[b,f]azepine moiety was more selective and most active against M. avium DHFR [19]. With the same motivation, Shoen et al synthesized 2,4-diamino-5-methyl-5-deazapteridines (DMDP) having structures similar to the trimetrexate/piritrexim and identified their antimycobacterial activity against M. avium complex (MAC) [20], in the continuation Suling et al established the DMDPs activity and selectivity towards the DHFR of MAC/Human [21]. Additionally, Meyer et al [22] and Gerum et al [23] also identified WR99210 (1,3,5-triazine derivative) and its analogues as potent inhibitors of MAC and M. tuberculosis DHFR, respectively.…”
Section: Introductionmentioning
confidence: 94%